Peran Research and Development (R&D) dalam Pengembangan Produk dan Relokasi Usaha: Studi Kasus Rumah Makan Iko Denai - Muhammad Taruna Sakti Batubara; Laura Natalia Naibaho; Lucky Sanjaya Rajagukguk; Lilis Elita Sinaga; Dionisius Sihombing; Marito Ritonga (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Small and medium enterprises (SMEs) often face limitations in implementing formal Research and Development (R&D), leading to reliance on informal practices based on experience and customer interaction. This study aims to examine how informal R&D contributes to product development and operational improvement in a small culinary business, namely Iko Denai Restaurant in Medan, Indonesia. A qualitative case study approach was employed, with data collected through in-depth interviews with the business owner and direct field observations. Source triangulation was applied to enhance data validity by comparing findings from different data sources. The results indicate that R&D activities are carried out informally through continuous interaction with customers, small-scale product trials, and ongoing evaluation of product quality and service. This approach enables the business to introduce new menu items with lower risk and adapt quickly to customer preferences. In addition, the decision to relocate the business to a more strategic location reflects a form of process innovation aimed at improving accessibility and customer convenience. The study highlights that informal R&D practices can effectively support innovation and business sustainability in SMEs, offering practical insights for small business development.